Uncovering new transition metal Zintl phases by cation substitution: the crystal chemistry of Ca3CuGe3 and Ca2+nMnxAg2−x+zGe2+n−z (n = 3, 4). Issue 14 (17th March 2021) - Ponou, Siméon; Miller, Gordon J.; Mudring, Anja-V.
Abstract : Crystal engineering in transition metal Zintl phases. Abstract : High-temperature solid-state reactions of the respective elements afforded the new transition metal Zintl phases Ca3 CuGe3 (Sc3 NiSi3 type, monoclinic C 2/ m – i 7, Pearson code mC 28), Ca6 Mn x Ag2− x + z Ge6− z (own type, monoclinic P 21 / m – e 14, Pearson code mP 28) and, Ca5 Mn x Ag2− x + z Ge5− z (Ca5 MgAgGe5 type, orthorhombic Pnma – c 12, Pearson code oP 48) as evidenced by single-crystal X-ray diffraction. They are additional representatives of the recently discovered homologous series Ca2+ n M2+ z Ge2+ n − z, already reported with M = Ag, Mg. These new phases were rationally prepared, after speculation that Cu and Mn could replace the isovalent Ag and Mg, respectively, to yield isostructural phases. Their crystal chemistry is discussed using established 'structure directing rules'. Their structures are best described according to the Zintl–Klemm formalism as (Ca 2+ )(2+ n ) [M2+ z Ge2+ n − z )] 2(2+ n )− featuring (poly-)germanide oligomers, [Ge n ] (2 n +2)− with n = 1–5. These Zintl anions interact with the highly polarizing small M (Cu, Ag, Mn) cations through their terminal Ge atoms, while the central Ge atoms are in trigonal prismatic coordination with the active metal Ca . Electronic structure calculations using density functional theory (DFT) were conducted on the idealized fully ordered model of "Ca3 MGe3 " (Sc3 NiSi3 type) with M = Cu, Ag for an analysis of the chemical bonding and structure stabilizing factors. Our findings suggest that new transition metal Zintl phases can be obtained through partial to complete replacement of the highly polarizing small s-block cations (Li, Mg) in the Ca–(Li, Mg)–(Ge, Si) system by their isovalent transition metals like Ag, Cu, and Mn. However, due to differences in coordination requirements and possible strong metal–metal bonding between the d-block elements, the resulting transition metal phases may not be isostructural with their Li and Mg counterparts, even when featuring the same type of Zintl anions.